2019
DOI: 10.1299/jtst.2019jtst0002
|View full text |Cite
|
Sign up to set email alerts
|

Thermohydraulic performance evaluation of heat exchangers equipped with centrally perforated twisted tape: Laminar and turbulent flows

Abstract: Convective heat transfer enhancement in a round tube mounted with a centrally perforated twisted tape (CP-TT) was numerically investigated. Influences of space of cut ratio (s/w = 0.5, 0.7 and 0.9) and twist ratio (y/w = 2.0, 3.0 and 4.0) under laminar and turbulent flow regimes on heat transfer characteristics were determined. Numerical encompassed Reynolds numbers (Re) from 400 to 2000 for laminar flow and 5000 to 15,000 for turbulent flow. At a given Reynolds number, the tubes with centrally perforated twis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…1,4 Uses of multiple tapes inside the circular duct, perforated twisted tapes, notched tapes, spaced twisted tapes, v-cut type, and perforated tapes are a few cases of modification of the existing plane tape. [5][6][7][8] These studies revealed that insertion of the twisted tape will enhance the heat transfer rate. From the literature, it is also observed that twisted tapes perform well in laminar flow than that of turbulent flow.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…1,4 Uses of multiple tapes inside the circular duct, perforated twisted tapes, notched tapes, spaced twisted tapes, v-cut type, and perforated tapes are a few cases of modification of the existing plane tape. [5][6][7][8] These studies revealed that insertion of the twisted tape will enhance the heat transfer rate. From the literature, it is also observed that twisted tapes perform well in laminar flow than that of turbulent flow.…”
Section: Introductionmentioning
confidence: 97%
“…Plenty of research has been conducted by researchers in using either a full‐length twisted tape or modifications to the full length . Uses of multiple tapes inside the circular duct, perforated twisted tapes, notched tapes, spaced twisted tapes, v‐cut type, and perforated tapes are a few cases of modification of the existing plane tape . These studies revealed that insertion of the twisted tape will enhance the heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…They reported the maximum value of 1.27 for PEC numbers in the range of studied operational conditions. Ruengpayungsak et al [ 33 ] investigated centrally perforated twisted tape inserts numerically in both laminar and turbulent regimes. They reported the maximum value for PEC number equal to almost 8.92 and 1.33 for laminar and turbulent regimes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the range of their operational conditions, they presented a maximum PEC number equal to 1.27. Centrally perforated twisted tape elements in a tube were investigated by Ruengpayungsak et al [36] for convective heat transfer enhancement under laminar and turbulent flow regimes. Maximum PEC values of 8.92 and 1.33 were reported for laminar and turbulent regimes, respectively.…”
Section: Introductionmentioning
confidence: 99%